POLA PERILAKU KEAGAMAAN DAN KEARIFAN LOKAL (Studi Kualitatif tentang Perilaku Keagamaan dan Kerifan Lokal di Negeri Mamala Kecamatan Leihitu Kabupaten Maluku Tengah) - Pardianto Pardianto (DIALEKTIKA, 2020)
ABSTRACT This study is an action research to develop the potential of students toward the creation of a community of students who proactively promote the issue of climate change and synergize the potential of students in integrating disaster reduction in the context of climate change on coastal and small island communities. This studies using two methods are Community-Based Research and Asset-based Community Empowerment. The results of the study are as follows. The development of students' potential to promote climate change is well placed to do given the students are change agents are expected to play a major role in the preservation of nature amid the threat of environmental damage become apparent. In order to synergize the potential of students in integrating disaster reduction in the context of climate change on small island coastal communities need to do some strategy. In this study, conducted workshops during the three days with two activities, namely an understanding of climate change through the medium of video and mentoring training assess the vulnerability of coastal communities to climate change. The understanding of climate change through the medium of video is intended to give an idea of what the global climate change. There are four categories of videos watched by the participants, namely (1) the introduction of global climate change, (2) the impact of climate change in different parts of the world, (3) adaptation to climate change in several places in Asia, and (4) instructions to adaptation as well as campaigning for adaptation to society. Training of community assistance is intended to prepare students as facilitators assisting the community in assessing the vulnerability of coastal communities in a participatory social and community together with preparation preparing climate change adaptation strategies. Keywords: Climatic video, climate change education, vulnerability assesment, climate assistance